2023
DOI: 10.1038/s41467-023-39114-z
|View full text |Cite
|
Sign up to set email alerts
|

Spectral signatures of a unique charge density wave in Ta2NiSe7

Abstract: Charge Density Waves (CDW) are commonly associated with the presence of near-Fermi level states which are separated from others, or “nested", by a wavector of q. Here we use Angle-Resolved Photo Emission Spectroscopy (ARPES) on the CDW material Ta2NiSe7 and identify a total absence of any plausible nesting of states at the primary CDW wavevector q. Nevertheless we observe spectral intensity on replicas of the hole-like valence bands, shifted by a wavevector of q, which appears with the CDW transition. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…4(f)]. As the gap is not positioned at E f and the spectrum weight diminishes away from the gap, it mainly comes from the intrinsic electronic hybridization between backfolded bands, instead of diffraction of the final states [46]. Meanwhile, no charge order gap at the Fermi level, which lowers the total electronic energy, is observed at this k z .…”
Section: Resultsmentioning
confidence: 87%
“…4(f)]. As the gap is not positioned at E f and the spectrum weight diminishes away from the gap, it mainly comes from the intrinsic electronic hybridization between backfolded bands, instead of diffraction of the final states [46]. Meanwhile, no charge order gap at the Fermi level, which lowers the total electronic energy, is observed at this k z .…”
Section: Resultsmentioning
confidence: 87%
“…The real-space dI/dV maps of the ML irregular step edge are shown in Figure 4d−j, showing a semblable energy dependence as described earlier. Additionally, the ESs always exist within a certain energy interval, ignoring complicated geometry and chemical environment, e.g., strain field, reconstructions, 29 However, a recent angle resolved photoemission spectroscopy (ARPES) study only found band backfolded behavior of Ta 2 NiSe 7 24 but could not trace any signs of topological surface states or Fermi wavevector nesting, which even contradicts other ARPES research, 25 indicating complicated electronic structures of Ta 2 NiSe 7 . We comment that the choices of exchange-correlation functionals, with/without SOC, tensile and shear stresses, and test temperatures can significantly affect the calculated topology of Ta 2 NiSe 7 .…”
Section: T H Imentioning
confidence: 94%
“…22 Besides, it was verified that the breakdown current density of an 18 nm Ta 2 NiSe 7 film is strikingly 35 times higher than that of copper. 23 The remarkable current-carrying behavior and CDW order in Ta 2 NiSe 7 suggest an exotic electronic structure, 24,25 which, however, has been rarely addressed hitherto, and its nonlinear optical response is still in its infancy.…”
mentioning
confidence: 99%
“…16 The synchrotron radiation X-ray diffraction experiments claimed that there are two independent CDW in Ta 2 NiSe 7 , with modulation wave vectors q and 2q, each corresponding to the transverse displacement of Ni and Se2 and the longitudinal modulation of Ta2, respectively. 22,23 However, the ARPES experiments identified the total absence of any plausible nesting of states at the primary wavevector q but suggested a possible nesting at 2q, 24 proving the CDW in Ta 2 NiSe 7 as a highly unusual case, different from the paradigmatic CDW materials. Further experimental and theoretical works are needed to fully understand the impact of the CDW state on the electronic structure in Ta 2 NiSe 7 .…”
mentioning
confidence: 95%
“…The effect of Fermi surface reconstruction arising from a CDW on the evolution of carrier concentration and mobility was observed by the measurements of transport properties in TiSe 2 and LaTe 3 . , In Ta 2 NiSe 7 , it has gone through an incommensurate CDW transition manifested as a small kink in the temperature dependence of resistivity . The synchrotron radiation X-ray diffraction experiments claimed that there are two independent CDW in Ta 2 NiSe 7 , with modulation wave vectors q and 2q , each corresponding to the transverse displacement of Ni and Se2 and the longitudinal modulation of Ta2, respectively. , However, the ARPES experiments identified the total absence of any plausible nesting of states at the primary wavevector q but suggested a possible nesting at 2q , proving the CDW in Ta 2 NiSe 7 as a highly unusual case, different from the paradigmatic CDW materials. Further experimental and theoretical works are needed to fully understand the impact of the CDW state on the electronic structure in Ta 2 NiSe 7 .…”
mentioning
confidence: 99%